Construction and deformation of curves and surfaces based on ?-sh basis functions with shape parameters - Zhang, Kewei; Wang, Han (Zielona Góra: Uniwersytet Zielonogórski)
Curve and surface modeling techniques have long been essential in computer graphics research. However, many existing methods for curve and surface fitting, as well as deformation, have limitations, such as challenges in representing certain special curve forms and a lack of control over the deformation process. Therefore, there is a need for a method that accurately represents specific curves and surfaces while allowing for a more intuitive and straightforward deformation implementation.
Keywords: hyperbolic sine function; curve and surface construction; shape parameter; deformation technique